The Implementation of the Eco-Pesantren Program in Environmental Management at Islamic Boarding Schools in West Lombok - Nawawi, Muhammad; Halid, Idham; Julaikha, Siti; Suhada, Adriyan (PROMOTOR, 2024)
Efforts to foster environmental awareness through environmental education will contribute greatly to preventing further environmental damage and even repairing damage that has already occurred. One approach model that can be developed is the Eco-Pesantren education. Study on the Application of Eco-Pesantren Program in environmental management is carried out at Islamic boarding schools in West Lombok Regency. This study aims to determine the implementation of the Eco-Pesantren program in Islamic boarding schools in West Lombok Regency towards environmental attitudes using the SWOT analysis method. This research was conducted in January to March 2017. Data collection techniques were carried out using data triangulation techniques (observation, interviews and questionnaires). Interviews were conducted using Snowball Sampling and questionnaires were conducted by taking 10% students at each pesantren. Based on the calculation, the percentage obtained for the development of environmentally friendly boarding school policy is 65%. For the development of an Islamic-based environmental curriculum by 32%. Development of natural curricular extra curricular based on 45%. Development of facilities and infrastructure supporting boarding schools by 33%. Based on the criteria for measuring attitudes obtained values> 60% -96%.